2019
DOI: 10.1021/acsomega.9b00904
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Isolation and Identification of Pneumonia-Associated Pathogens from Sputum Samples Combining an Innovative Sample Preparation Strategy and Array-Based Detection

Abstract: With this study, an innovative and convenient enrichment and detection strategy for eight clinically relevant pneumonia pathogens, namely, Acinetobacter baumannii , Escherichia coli , Haemophilus influenzae , Klebsiella pneumoniae , Moraxella catarrhalis , Pseudomonas aeruginosa , Staphylococcus aureus, and Streptococcus pneumoniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The data demonstrate that the most predominant bacterial species isolated was S. pneumonia among patients in Zakho hospital. This agreed with the results of Al-Hadrawi et al (2019) and Pahlow et al (2019), who found that the higher rate of isolated bacteria was S. pneumonia in sputum and urine.…”
Section: Discussionsupporting
confidence: 93%
“…The data demonstrate that the most predominant bacterial species isolated was S. pneumonia among patients in Zakho hospital. This agreed with the results of Al-Hadrawi et al (2019) and Pahlow et al (2019), who found that the higher rate of isolated bacteria was S. pneumonia in sputum and urine.…”
Section: Discussionsupporting
confidence: 93%
“…So far, much research has been done on infectious agents, and microarrays of some species have been designed. Multiplex PCR along with amplified PCR hybridization linked to specific probes in a microarray chip, is a multiparametric technology to diagnose bacteria causing the infection (104,108) . The Respiratory Multiplex Array is used to detect 22 respiratory pathogens simultaneously in people suffering from the respiratory tract infection.…”
Section: Pcr Microarray Technologymentioning
confidence: 99%